2019
DOI: 10.1177/1329878x19828366
|View full text |Cite
|
Sign up to set email alerts
|

‘Take it down!’: Estonian parents’ and pre-teens’ opinions and experiences with sharenting

Abstract: Semi-structured individual interviews with 14 Estonian mothers and their children (aged 9–13 years) pairs who had ‘friended’ each other on Facebook were carried out to study pre-teens’ and parents’ reflections and experiences regarding information disclosures and sharenting on Facebook. We wanted to know what kind of information mothers shared about their children on Facebook and how the children perceived and reacted to such posts. Our findings indicated that there was a major discrepancy in the parents’ and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 21 publications
0
33
0
4
Order By: Relevance
“…However, such concerns prioritized children's physical privacy and safety (boyd & Hargittai, 2010;Symons et al, 2019), which highlights the complexity of the privacy stewardship role parents have as well as the possible gaps between perceived risks and actual sharing behaviors. The complex boundary management processes between parents and children when it comes to sharenting are described by Lipu and Siibak (2019), who interviewed 14 Estonian mothers and their 9-to 13-year-old children, using communication privacy management (CPM; Petronio, 2002) theory. Their findings revealed instances of privacy turbulence, similar to the one described in the Introduction between Gwyneth Paltrow and her daughter Apple Martin, and showed the intricacies of privacy stewardship in practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, such concerns prioritized children's physical privacy and safety (boyd & Hargittai, 2010;Symons et al, 2019), which highlights the complexity of the privacy stewardship role parents have as well as the possible gaps between perceived risks and actual sharing behaviors. The complex boundary management processes between parents and children when it comes to sharenting are described by Lipu and Siibak (2019), who interviewed 14 Estonian mothers and their 9-to 13-year-old children, using communication privacy management (CPM; Petronio, 2002) theory. Their findings revealed instances of privacy turbulence, similar to the one described in the Introduction between Gwyneth Paltrow and her daughter Apple Martin, and showed the intricacies of privacy stewardship in practice.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest that privacy risk considerations are frequently present when parents recount their sharenting practices (Chalklen & Anderson, 2017;Lipu & Siibak, 2019) to the point of hindering their children-related posting behavior (Ammari et al, 2015). Parents who engage in sharenting employ a series of practices to preserve their children's privacy.…”
Section: Parents and Privacymentioning
confidence: 99%
See 1 more Smart Citation
“…The four types of communicative orientation characterize the parental approach to sharenting including the family-oriented approach, peer-oriented approach, opposition, and not using [28]. The results showed that the ten subjects in this research conducted sharenting that included a peer-oriented approach.…”
Section: Ways Of Millennial Parents Conduct Sharentingmentioning
confidence: 78%
“…As children grow older, parents transition from being the exclusive decision maker about sharing photos of their children online to a situation where children start exercising their voice and opinion about what should, and should not, be shared online. At times this can lead to 'boundary turbulence' in that the privacy expectations of children and their parents may not align, and difficult but important conversation can ensue (Lipu & Siibak, 2019). As children grow and usually start using their own social media accounts, their desire to shape their own identities and personality online can conflict with parental sharing, although in some contexts these conversations, too, can often be very productive with new boundaries and expectations emerging (Ouvrein & Verswijvel, 2019).…”
Section: Sharenting Ultrasounds and Beyondmentioning
confidence: 99%